Kingston draft and the requirement of intellectual, analytical ability and sound judgement in making appointments to the Office of Judge of the proposed Caribbean Court of Justice - McDowell, Zanifa (1997)
Reviews the various arguments for and against retention of the Privy Council. Provides analyses of local cases overturned by the Privy Council which will go some way in providing the empirical data needed to support the argument that local decisions are often inferior to Privy Council decisions.